Subversão da verdade : o ecossistema da desinformação na origem da crise democrática na era da pós-verdade - Caldeira, Helder de Oliveira (2023)
The object of the study is to answer, considering that post-truth brings with it elements of influence on the rule of law and the result of the research by Vosoughi, Roy and Aral, from MIT (USA) on the speed of traffic of misinformation and fake news in the main contemporary means of communication which are social networks, what are the impacts caused by the subversion of truth in the crisis of democracy. The theoretical framework, first of all, supports the existence of a sui generis crisis in the democratic regime. In search of the origin of the problem, the Advisory Opinion OC-5/85 of the Inter-American Court of Human Rights and the discourse and tone of the ruling of the Supreme Federal Court in RE 511.961/SP were revisited. Under the scrutiny of extensive bibliography, the pillars of the hypothesis were erected. If the existence of the democratic rule of law is intrinsically conditioned to the objective truth of the facts and the corresponding fundamental right to truth, the ecosystem of subversion of truth is a point of contamination of the social phenomenon. The impacts of misinformation and fake news on the democratic rule of law were studied, verified and presented, in terms of objective truth of the facts in Brazil, as well as the antidotes that can be used by Brazilian authorities to try to regulate the phenomenon in accordance with the Constitution and in the context of conventionality control, without slipping into prior censorship and banning of social network users and other contemporary communication structures.